Women empowerment through health seeking behavior in Bangladesh: Evidence from a national survey (South East Asia Journal of Public Health, 2016)
Empowering women is an important subject to achieve targets for the Sustainable Development Goals (SDGs) of Bangladesh. There are several indicators to measure the empowerment of women. Health seeking information is one of the most important indicators in this regard. This study aims at identifying the levels and patterns of women empowerment in relation to health seeking behavior in Bangladesh. Bangladesh Demographic and Health Survey (BDHS) 2011 data was used for the study. A total of 16635 women of reproductive age were included in this study. Only 42% of recently married women participated in all the four discussions regarding their own health care, major household purchases, child health care, and visiting their family or relatives. Cross tabulation and logistic regression analyses were performed to know about women empowerment in relation to health seeking behavior on decision making, controlling the effect of other independent variables. The results showed that about 63% women were empowered (either by themselves or jointly with their husbands) to decide on their own healthcare seeking and around 67% in healthcare seeking for their children. Working women were 1.734 times more likely to seek their own healthcare than non-working women. Again rural women appeared to be 21% less likely to seek child healthcare compared to urban women. The results of this study showed that seeking health information empowered women to promote their self-confidence, filter the information, manage life problems successfully, feel strength against health problems and disabilities, and be encouraged to seek more information.South East Asia Journal of Public Health Vol.6(1) 2016: 40-45